Ageism in the European Region: findings from the European Social Survey - Swift, H. J. (2018)
The Ageism module fielded in the 2008–2009 European Social Survey (ESS) across 29 representative samples in the European region (with over 55,000 respondents) is the first major internationally comparable study of individual and societal attitudes to age differences, and ageism. This chapter provides an overview and a review of what has been discovered. The chapter will introduce the module and the theoretical and empirical issues it was designed to address. Many of these issues are framed in terms of social psychological theories of prejudice and discrimination and the approach aimed to provide a robust measurement framework for capturing experiences and expression of ageism in different countries. Drawing on empirical work that has used the ESS data the chapter will review and summarise key discoveries and insights, showing how the module has been used to further understanding of how frequently ageism is experienced and how it is expressed in countries within the European region. The chapter highlights the value of the ESS data for understanding ageism and comments briefly on methods such as multilevel analysis for exploring ESS survey data on ageism.